Employment risk and job-seeker performance - Godlonton, Susan (International Food Policy Research Institute, 2014)
This paper examines the relationship between employment risk and job-seeker performance. To induce exogenous variation in employment risk, the outside options for job seekers undergoing a real recruitment process were randomized by assigning them a 0, 1, 5, 50, 75, or 100 percent chance of real alternative employment of the same duration and wage as the jobs for which they were applying. The findings show that job-seeker performance is highest and effort is lowest among those assigned the lowest employment risk (a guaranteed alternative job), and performance is lowest and effort highest among those facing the highest employment risk (those without any job guarantee). Moreover, a nonlinear relationship exists between employment risk and performance.